Demand response programs in smart grids – survey - H. Al-Kharsan, Ibrahim; Z. Ghazi Zahid, Ali; F.Marhoon, Ali.; Radhi Mahmood, Jawad (International Journal of Engineering and Technology, 2019)
The smart grid in this century has an essential role in changing the philosophy of the electrical power engineering. In the past, the generation must be equal to the demand under any situation but with the introduction of the non-conventional grids everything is changed, and the customers should consume energy in the same amount to what already generated from the generation units. The tool to achieve all that is the demand response (DR) strategy. DR can alter the consumption pattern of the consumers to make it flatting instead of the sharp curves that lead to additional costs coming from the increasing generating in the periods of the peaks in the load curve. In this paper, the demand response programs listed and discussed with an indication to the documents that deal with each type.
Keywords: Smart Grid; Demand Response; Demand Side Management; Load Scheduling; Smart Metering and Bidding Strategy.